2004
DOI: 10.1063/1.1644149
|View full text |Cite
|
Sign up to set email alerts
|

Low viscosity contrast fingering in a rotating Hele-Shaw cell

Abstract: We study the fingering instability of a circular interface between two immiscible liquids in a radial Hele-Shaw cell. The cell rotates around its vertical symmetry axis, and the instability is driven by the density difference between the two fluids. This kind of driving allows studying the interfacial dynamics in the particularly interesting case of an interface separating two liquids of comparable viscosity. An accurate experimental study of the number of fingers emerging from the instability reveals a slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 26 publications
12
74
1
Order By: Relevance
“…These phenomena can also be observed by contours of vorticity, depicted in Figure 2(c). The new layer presents outgoing ÿngers, which develop a peculiar fork-like shape, which is also identiÿed in immiscible situation [7], at t = 20. Besides, compared to the reference case, the ÿngering pattern clearly shows a rotational trend because of the stronger Coriolis e ects induced by the faster rotating speed.…”
Section: E Ects Of Control Parameters In a Constant Gap Width Cellmentioning
confidence: 99%
“…These phenomena can also be observed by contours of vorticity, depicted in Figure 2(c). The new layer presents outgoing ÿngers, which develop a peculiar fork-like shape, which is also identiÿed in immiscible situation [7], at t = 20. Besides, compared to the reference case, the ÿngering pattern clearly shows a rotational trend because of the stronger Coriolis e ects induced by the faster rotating speed.…”
Section: E Ects Of Control Parameters In a Constant Gap Width Cellmentioning
confidence: 99%
“…Based on the Hele-Shaw theory, Alvarez-Lacalle et al [2] investigated the interfacial instabilities of immiscible fluids in a rotating cell both experimentally and numerically, in which Coriolis forces are neglected. Finger pinch-off and droplet emission are detected at the low viscosity contrast and the low surface tension in their experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and experimental works have been carried out to study the interfacial instability in an annular Hele-Shaw cell [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These works have been extended to include effects arising from a constant rotation rate of the system and have mainly focused on the study of the linear growth rate, also, on the understanding fingering mechanisms of the interface when one of two immiscible fluids is accelerated toward the other under centrifugal forces.…”
Section: Introductionmentioning
confidence: 99%
“…In his work, the coriolis force is included in an ad hoc manner and it was shown that circular drop is unstable both to a translation, and depending on the rotation rate, to a number of fingering modes. Later on, the linear stability analysis originally performed in [2] has been extended to an arbitrary density and viscosity contrast by carrillo et al, [3][4][5], and to a low viscosity contrast flows by Alvarez-Lacalle et al [8]. In [3], Carrillo et al have studied, both theoretically and experimentally, the behavior of the interface between two immiscible fluids in a rotating Hele-Shaw cell when the inner fluid is injected, with constant injection rate, through a hole at the rotation axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation